Targeting keystone species helps restore the dysbiosis of butyrate‐producing bacteria in nonalcoholic fatty liver disease. Issue 4 (16th November 2022) - Wu, Dingfeng; Liu, Lei; Jiao, Na; Zhang, Yida; Yang, Li; Tian, Chuan; Lan, Ping; Zhu, Lixin; Loomba, Rohit; Zhu, Ruixin
Abstract: The dysbiosis of the gut microbiome is one of the pathogenic factors of nonalcoholic fatty liver disease (NAFLD) and also affects the treatment and intervention of NAFLD. Among gut microbiomes, keystone species that regulate the integrity and stability of an ecological community have become the potential intervention targets for NAFLD. Here, we collected stool samples from 22 patients with nonalcoholic steatohepatitis (NASH), 25 obese patients, and 16 healthy individuals from New York for 16S rRNA gene sequencing. An algorithm was implemented to identify keystone species based on causal inference theories and dynamic intervention simulation. External validation was performed in an independent cohort from California. Eight keystone species in the gut of NAFLD, represented by Porphyromonas loveana, Alistipes indistinctus, and Dialister pneumosintes, were identified, which could efficiently restore the microbial composition of the NAFLD toward a normal gut microbiome with 92.3% recovery. These keystone species regulate intestinal amino acid metabolism and acid–base environment to promote the growth of the butyrate‐producing Lachnospiraceae and Ruminococcaceae species that are significantly reduced in NAFLD patients. Our findings demonstrate the importance of keystone species in restoring the microbial composition toward a normal gut microbiome, suggesting a novel potential microbial treatment for NAFLD. Abstract : In this study, we applied an algorithm to the keystone species identification in the gut microbiome, based on current causal inference theories and the dynamic intervention simulation. We identified the nonalcoholic steatohepatitis (NASH) keystone species combination, represented by Porphyromonas loveana, Alistipes indistinctus, and Dialister pneumosintes, that showed the highest potential for the microbial intervention of NASH. Highlights: The dysbiosis of butyrate‐producing bacteria is a critical factor contributing to the development of nonalcoholic fatty liver disease (NAFLD). Causal algorithm intergraded with ecological theory and dynamic intervention simulation could mine microbial keystone species from metagenomic data. Keystone species of nonalcoholic steatohepatitis, such as Porphyromonas loveana, Alistipes indistinctus, and Dialister pneumosintes, provided potential precise intervention strategies for NAFLD treatment.